2020
DOI: 10.1186/s13104-020-05330-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of spinal anaesthesia in neonates and infants in Antananarivo, Madagascar: a retrospective descriptive study

Abstract: Objective The aim of this study was to present the first cases of spinal anesthesia, in newborns and infants, preterm/ex-prematures, in order to determine its feasibility and its potential harmlessness, in Antananarivo—Madagascar. Indeed, spinal anesthesia is a low cost technique and can limit respiratory complications, postoperative apnea a contrario with pediatric general anesthesia which can lead to perioperative risks. Results In a retrospective, descriptive, 7-year (2013 to 2019) period study, conducted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…Spinal anaesthesia was successful in 96.8%. these findings are similar to studies reported by Randriamizao et [2,6,12,16]. Only 6% of the patients needed conversion to GA.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Spinal anaesthesia was successful in 96.8%. these findings are similar to studies reported by Randriamizao et [2,6,12,16]. Only 6% of the patients needed conversion to GA.…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to findings by Williams et al in their study titled the safety and Efficacy of spinal anaesthesia for Surgery in infants [2]. Similar results (94.2%) were obtained by Randriamizao et al, and 95.3% were reported successful by Kachko L et al [6,11] In a meta-analysis to determine whether SA reduces intraoperative and postoperative complications compared with GA, Dorms K et al reported that SA is at least as safe as GA for inguinal hernia repair in preterm neonates [12].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…New data on the safety and efficacy of anesthesia experiences similar phenomenon. Anesthesiologists should be encouraged regional/neuraxial anesthesia in children continues to emerge from all over the world, even in remote settings such as rural Madagascar [16]. As the field of acute pain management and regional anesthesia continues to grow, the field of pediatric regional anesthesia experiences similar phenomenon.…”
Section: Discussionmentioning
confidence: 99%